Copper-67-Labeled Bombesin Peptide for Targeted Radionuclide Therapy of Prostate Cancer - Truc T. Huynh; Ellen M. van Dam; Sreeja Sreekumar; Cedric Mpoy; Benjamin J. Blyth; Fenella Muntz; Matthew J. Harris; Buck E. Rogers (MDPI AG, 2022)
The gastrin-releasing peptide receptor (GRPR) is a promising molecular target for imaging and therapy of prostate cancer using bombesin peptides that bind to the receptor with high affinity. Targeted copper theranostics (TCTs) using copper radionuclides, 64Cu for imaging and 67Cu for therapy, offer significant advantages in the development of next-generation theranostics. [64Cu]Cu-SAR-BBN is in clinical development for PET imaging of GRPR-expressing cancers. This study explores the therapeutic efficacy of [67Cu]Cu-SAR-BBN in a pre-clinical mouse model. The peptide was radiolabeled with 67Cu, and specific binding of the radiolabeled peptide towards GRPR-positive PC-3 prostate cancer cells was confirmed with 52.2 ± 1.4% total bound compared to 5.8 ± 0.1% with blocking. A therapy study with [67Cu]Cu-SAR-BBN was conducted in mice bearing PC-3 tumors by injecting 24 MBq doses a total of six times. Tumor growth was inhibited by 93.3% compared to the control group on day 19, and median survival increased from 34.5 days for the control group to greater than 54 days for the treatment group. The ease and stability of the radiochemistry, favorable biodistribution, and the positive tumor inhibition demonstrate the suitability of this copper-based theranostic agent for clinical assessment in the treatment of cancers expressing GRPR.